William Shakespeare, Macbeth - McLuskie, Kathleen (Writers and their work (Unnumbered), 2009)
This study explores the structure & theatricality of Macbeth; addresses the way that it was constructed as a work by its publication in the 1623 'Folio of Shakespeare's Works'; examines the relationship between that work & the history of its creation & reception; & analyses the role of the work in the imagined life of Shakespeare.